FAKTOR EKSTERNAL DAN INTERNAL PENGELOLAAN DESTINASI WISATA BERKELANJUTAN DI DESA WISATA MALANGAN YOGYAKARTA - Irma Kharisma Hatibie; Hesti Purwaningrum (Tulisan Ilmiah Pariwisata (TULIP), 2021)
The rural tourist attraction of Malangan, Sumberayu Moyudan, is one of the tourist rural destination in the Yogyakarta Regency which is also affected by the rampant development of rural-based tourism products. Although this tourist village has received special interest from tourists, it does not mean that every tourist village can survive and present tourism products that can continue to attract tourists to come. In that case, strategic action is needed in destination destinations, such as observations, observing all aspects related to destination sustainability. This is due to the increasing number of tourist villages in an area, there will be many competitors or competitors, as a result, there will be fierce competition or even unhealthy competition between tourism village managers. This research was conducted to answer the challenge of the importance of management that is right on target at the destination, while still paying attention to the principles of the existence of a tourist village built using a SWOT analysis. The result of this research is to present a destination management strategy based on an analysis of external and internal factors, which includes the strengths, weaknesses, opportunities, and threats of each category.